Faktor risiko leptospirosis di provinsi yogyakarta dan sekitarnya - Berry Murtiningsih, Setyawan Budiharta dan Suharyanto Supardi (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Leptospirosis is a community health problem in Indonesia. The result of spot surveys conducted by the Ministry of Health during 1994-1996 in five provinces showed the prevalence of positive leptospirosis specimens between 64.5% and 92.8%. During the post flood period in Jakarta in 2002, there was 27 leptospirosis cases with seven deaths. The hospital based leptospirosis surveillance in Yogyakarta Province showed an increase of leptospirosis cases with the most prevalent cases in the year 2000 (as high as 27 cases). Material and Methods: The objective of this study was to investigate factors related in human leptospirosis in Yogyakarta Province and its surrounding areas. A hospital and community based, sex-matched, case-control design was used the study. Study subjects include 53 leptospirosis cases and 53 controls. Risk factors studied included rice farming, raising domestic animals, existence of domestic animals in the neighbor, rats in the house, bathing habit in the river, washing clothes in the river, fishing, swimming, looking for eel and frog in the farm, water recreation and going to rice field. Data are analyzed using univariate analysis, stratification analysis and multivariate analysis. Results: The study revealed that factors associated with leptospirosis were rice farming (OR=4,7; 95% Cl= 1,2 – 17,9), habit of going to the rice field (OR=4.1; 95% Cl= 1.18 – 14,1) rats in the house (OR=6,9; 95% CI=1,7 – 24,5) and looking for eel and frog in the farm (OR=3,9; 95% Cl= 1,0 – 14,6) are significant risk factors of leptospirosis. Conclusion: Risk factors associated with leptospirosis in Yogyakarta province and its surrounding areas include rice farming, going to the rice field, rats in the house and looking for eel and frog in the farm. Keywords: Leptospirosis, risk factors, case-control study